2012
DOI: 10.1007/s12029-012-9455-5
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Emergency and Non-emergency Colorectal Cancer Surgeries in West Virginia and the USA

Abstract: Purpose Elective surgical resection is the curative treatment for colorectal cancer (CRC). Up to 30 % of patients present as surgical emergencies. The objective was to determine the association between presenting with an emergency condition and consequent outcomes of CRC surgery in the Appalachian state of West Virginia (WV) in comparison to the rest of the USA. Methods Patients diagnosed with CRC who underwent a surgical procedure from January 1, 2003 to December 31, 2007 were selected, and those with a dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 27 publications
(25 reference statements)
0
17
0
1
Order By: Relevance
“…The important finding is that half of all surgical procedures performed in this population are done on an emergent basis, which is independently associated with worse outcomes as seen in our results and other studies. 12 Diverticular disease is the most common indication for colon surgery in the kidney transplant population, accounting for 48 per cent of cases. Several studies have shown an increased incidence of acute diverticulitis in the kidney transplant population.…”
Section: Discussionmentioning
confidence: 99%
“…The important finding is that half of all surgical procedures performed in this population are done on an emergent basis, which is independently associated with worse outcomes as seen in our results and other studies. 12 Diverticular disease is the most common indication for colon surgery in the kidney transplant population, accounting for 48 per cent of cases. Several studies have shown an increased incidence of acute diverticulitis in the kidney transplant population.…”
Section: Discussionmentioning
confidence: 99%
“…However, the management of diseases which are commonly encountered by ACS services do not usually require long-term surveillance for disease recurrence [ 16 , 20 ]. The acute care of emergency CRC patients therefore presents a relatively more complex challenge as it requires the coordination of multiple specialties, including gastroenterologists, surgeons, and oncologists (medical and/or radiation) [ 2 , 3 , 5 , 8 ]. While ACS services in the United States are typically staffed by subspecialty trauma and acute care surgeons [ 19 , 20 ], many Canadian ACS teams are run by surgeons who also routinely perform cancer operations as part of their elective practices [ 14 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The latter one was previously considered a first-choice procedure in emergency colon surgery since it is fast to perform and prevents anastomotic leakage, but it requires a second stage to reverse the colostomy [38]. Therefore, there has been reported a shift regarding the surgical approach with a higher rate of one-stage procedure being performed [6,39, 40, 41]. Many studies, however, still report an increasing number of surgical procedures involving the creation of a diverting stoma in elderly patients [42].…”
Section: Discussionmentioning
confidence: 99%